89.5k views
4 votes
Use first principle to find y'all for y=xe^x

User Foobnix
by
4.7k points

1 Answer

0 votes

By definition of the derivative,


y'=\displaystyle\lim_(h\to0)\frac{(x+h)e^(x+h)-xe^x}h

We can employ the standard manipulation for proving the product rule:


\displaystyle\lim_(h\to0)\frac{(x+h)e^(x+h)-xe^(x+h)+xe^(x+h)-xe^x}h


\displaystyle\lim_(h\to0)\frac{(x+h)e^(x+h)-xe^(x+h)}h+xe^x\lim_(h\to0)\frac{e^h-1}h


\displaystyle\lim_(h\to0)e^(x+h)\lim_(h\to0)\frac{(x+h)-x}h+xe^x\lim_(h\to0)\frac{e^h-1}h


e^(x+0)\displaystyle\lim_(h\to0)\frac hh+xe^x\lim_(h\to0)\frac{e^h-1}h


e^x+xe^x\displaystyle\lim_(h\to0)\frac{e^h-1}h

The remaining limit is pretty well-known and has a value of 1. We can derive it from the definition of
e,


e=\displaystyle\lim_(n\to0)(1+n)^(1/n)

In the limit above, we substitute
\eta=e^h-1, so that
h=\ln(\eta+1). As
h\to0, we have
\eta\to e^0-1=0:


\displaystyle\lim_(h\to0)\frac{e^h-1}h=\lim_(\eta\to0)\frac\eta{\ln(\eta+1)}


\displaystyle=\lim_(\eta\to0)\frac1{\frac1\eta\ln(\eta+1)}


\displaystyle=\frac1{\lim\limits_(\eta\to0)\ln(\eta+1)^(1/\eta)}


\displaystyle=\frac1{\ln\left(\lim\limits_(\eta\to0)(\eta+1)^(1/\eta)\right)}


=\frac1{\ln e}=\frac11=1

After all this, we've shown that


(xe^x)'=e^x+xe^x=e^x(x+1)

User Peshkira
by
5.4k points